c-FOS Expression in Metastatic Basal Cell Carcinoma with Spontaneous Basosquamous Transition - Yu Kurokami; Yosuke Ishitsuka; Eiji Kiyohara; Atsushi Tanemura; Manabu Fujimoto (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)